Use of low-intensity laser radiation in sports activity of boxers - D.S. Melnikov; Yu.A. Shchedrina (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify changes in the regulation of the heart rhythm in highly skilled boxers in the preparatory period against the background of the potentiating effect of low-intensity laser radiation (LILR). Methods and structure of the study. To solve the problems, a seven-course effect of LILR was used. To register the desired parameters of heart rate variability, the Omegawave V.4. hardware-software complex was used. Processing, analysis and subject study of the research materials were carried out using the methods of mathematical statistics. Results and conclusions. After stimulation with LILR, signs of optimizing the functional state of boxers were found: an increase in RMSSD by 28.1% was observed; TR by 27.3%, the contribution of HF waves to the total spectrum by 101% (at p<0.05); VLF by 41.7%, as well as a decrease in the stress index by 30.8% and LF / HF by 44.9%. The data obtained indicate an increase in cerebral ergotropic and humoral-metabolic reactions under the influence of the course application of LILR. Conclusions. The efficiency of using low-intensity laser radiation as a means of stimulating recovery processes after intense situational loads of various powers has been established.